(untitled) ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2015)
Background: Obesity is a complex multi factorial chronic disease developing from the interactive influences of numerous factors—social, behavioral, psychological, metabolic, and genetic. Obesity invites disability, diseases like atherosclerosis, high blood pressure, stroke, diabetes, bone disorders and premature death. Objective: The objective of the study was to check the prevalence of overweight and obesity among the geriatric population, by assessing their nutritional and health status. Methods: Subjects (n=100) both males and female equal in number, ranging in age from 60- 90 years residing in the urban areas of west Delhi, India were selected. Socio-demographic details and anthropometrical measurements like weight, height, BMI and WHR were assessed. Results: Mean weight for males and females (73.1 and 64.3 kg) respectively was found to be higher than the reference weight. Height seems to be decreased with the advancing age among the samples. Mean BMI for females (26.7 kg/m2) was higher than that of the males (25.4 kg/m2). Prevalence of overweight was found to be 48% in males and 36% in females. Prevalence of obesity was higher in females (24%) than males (8%). Mean values for WHR was higher than the cut offs given by WHO among the females, contributing to prevalence of abdominal adiposity. Conclusion: Overweight and obesity in the geriatric population has been found to be increasing in the urban settings of India which is a challenging task for healthy India.